Characterization of immunogenic protein fractions of Sheep Cysticercosis in Cairo, Egypt - MAHDY, O. A.; MOUSA, W. M.; ABDEL-MAOGOOD, S. Z.; ABDEL-RADI, S.; EL-BAHY, M. M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Cysticercosis is a parasitic infection that causes severe economic and public health problems. The overall incidence of infection in sheep slaughtered in Cairo, Egypt during meat inspection was 31.22% and precisely 19.72% for Cysticercus tenuicollis and 11.50% for C. ovis. Sera collected from infected animals used to evaluate the diagnostic efficacy of the extracted antigens using ELISA. The sensitivity of the test was 100% for both C. tenuicollis and C. ovis, while the specificity was 80.26% and 87.03%, respectively. Using EITB the fractions of 36 KDa and 23 KDa appears to be specific for diagnosis of C. tenuicollis; while, 77 KDa and 73 KDa were specific for diagnosis of C. ovis. Moreover, several protein fractions which were detected in all antigens extracted didn’t react with its target sera but at the same time did react specifically versus sera from animals infected with another cysticerci. Those fractions are considered as common immunogenic fractions between different cysticerci, so strictly identified specific fractions must to be used for diagnosis of Cysticerci infection to avoid cross reactions with other cysticerci antibodies.